Thrombus composition and distribution patterns by thrombus volume in acute ischemic stroke - Yun, Jaeseob; Jung, Jae Wook; Kim, Kwang Hyun; Nam, Hyo Suk; Heo, JoonNyung; Lee, Hyungwoo; Kim, Byung Moon; Kim, Dong Joon; Baik, Minyoul; Yoo, Joonsang; Kim, Jinkwon; Park, Hyungjong; et al. (Frontiers in Neurology, 2025)
BackgroundThrombus burden considerably impacts ischemic stroke presentation and outcomes. However, the relationship between thrombus histology and volume has not been studied well. We investigated whether ischemic stroke thrombus composition and spatial distribution patterns differed with thrombus volume.MethodsWe enrolled patients with thrombi undergoing endovascular therapy (EVT) between July 2017 and July 2023. Thrombus volume on thin-section non-contrast computed tomography was measured using three-dimensional software. Immunohistochemistry analysis included fibrin, red blood cells (RBCs), and platelets. Thrombi were classified based on the overall distribution pattern of the components: layered, erythrocytic, mixed, and diffuse platelet. We analyzed the association between thrombus volume, histopathology, distribution patterns, and clinical/radiologic outcomes.ResultsAmong 210 patients, the median (interquartile range) thrombus volume was 43.7 (23.5, 74.5) mm3. Increased thrombus volume correlated with high RBC proportion (r = 0.359, p < 0.001) and low platelet proportion (r = −0.194, p = 0.005). Thrombus volume was independently related to the RBC proportion (β 1.00, standard error [SE] 0.27, p < 0.001), mixed (β 21.04, SE 10.10, p = 0.038), and erythrocytic pattern (β − 29.78, SE 11.54, p = 0.011). The number of fragmented thrombi during the procedure was independently related to thrombus volume (β 0.006, SE 0.002, p = 0.006) and RBC proportions (β 0.18, SE 0.009, p = 0.049).ConclusionLarge thrombi had increased RBC proportions and a mixed pattern. RBC incorporation significantly contributes to the volumetric growth of thrombi and their fragmentation susceptibility. These findings may provide additional clue for tailoring EVT strategies.